Climate change adaptation in the Nigerian agricultural sector - Schmitt-Olabisi, Laura; Liverpool-Tasie, Lenis Saweda; Onyeneke, Robert; Choko, Onyinye; Osuntade, Bukola; Sanou, Awa; Singa, Udita; Chiemela, Stella Chude (Michigan State University, 2019)
West Africa is expected to suffer yield and production losses of staple crops under climate change, with more severe yield reductions occurring in the period between 2030 and 2050 (Ittersum et al., 2016). In addition, extreme events, including droughts and floods, are expected to become more frequent under climate change, also potentially affecting yields (Abiodun, Lawal, Salami, & Abatan, 2013). Internal displacement and natural resource conflicts are another expected climate impact, as are pest and disease outbreaks (Gregory, Johnson, Newton, & Ingram, 2009; Obioha, 2008). Given these potentially serious climate impacts, a team comprising researchers from Michigan State University and Nigerian partner universities conducted studies intended to inform Nigerian agricultural policy around climate adaptation. This brief presents a summary of findings from 4 of these studies conducted between 2016 and 2019.